Nonlinearity in cap-and-trade systems: The EUA price and its fundamentals - Benjamin Johannes Lutz; Uta Pigorsch; Waldemar Rotfuß (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
In this paper we examine the nonlinear relation between the EUA price and its fundamentals, such as energy prices, macroeconomic risk factors and weather conditions. By estimating a Markov regime-switching model, we find that the relation between the EUA price and its fundamentals varies over time. In particular, we are able to identify a low and a high volatility regime, both showing a strong impact of the fundamentals on the EUA price. The high volatility regime is predominant during the recession of 2008 and 2009 - a time period in which the actual emissions sharply decreased due to the economic crisis.
urn:nbn:de:bsz:180-madoc-330020
Keywords: C22; C58; G13; Q50; 330; EU ETS; EUA Price Fundamentals; Markov Regime-Switching